Development of A Down Passing Training Model Through Target Media for Volleyball Athletes - Gustiar, Mailudiana Juan; Imansyah, Farizal; Sari, Puput Sekar (Universitas PGRI Palembang, 2025)
This study aims to develop an innovative and structured training model for the basic underhand pass technique in volleyball using target media as a training aid. The research subjects were adolescent athletes from PBV Tunas Inti Sriwijaya who are currently undergoing a development program. The method used was Research and Development (R&D) with the ADDIE model approach, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. During the development stage, validations were conducted by volleyball technique experts and media experts to assess the feasibility of the product. The validation results showed that the developed training model was highly valid, with an average score of 96.66%. Furthermore, small-scale and large-scale trials were conducted on different groups of athletes, and the results indicated a practicality level of 90.00%, categorized as highly practical. The resulting product consists of a training manual and a training model video that incorporates target media exercises to improve the accuracy of direction and control in underhand passing. This training model has proven effective in enhancing basic technical skills, athlete motivation, and engagement during training sessions. Therefore, the product can serve as an effective and innovative alternative solution for coaches and clubs in designing more systematic and enjoyable training programs.